2017
DOI: 10.1038/s41598-017-01823-z
|View full text |Cite
|
Sign up to set email alerts
|

Frequent heteroplasmy and recombination in the mitochondrial genomes of the basidiomycete mushroom Thelephora ganbajun

Abstract: In the majority of sexual eukaryotes, the mitochondrial genomes are inherited uniparentally. As a result, individual organisms are homoplasmic, containing mitochondrial DNA (mtDNA) from a single parent. Here we analyzed the mitochondrial genotypes in Clade I of the gourmet mushroom Thelephora ganbajun from its broad geographic distribution range. A total of 299 isolates from 28 geographic locations were sequenced at three mitochondrial loci: the mitochondrial small ribosomal RNA gene, and the cytochrome c oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
4
10
0
Order By: Relevance
“…Our results add up to the expanding list of basidiomycete mitogenomes that have displayed evidences of hybridization and recombination (Xu et al. 2009; Wang et al. 2017).…”
Section: Discussionsupporting
confidence: 62%
“…Our results add up to the expanding list of basidiomycete mitogenomes that have displayed evidences of hybridization and recombination (Xu et al. 2009; Wang et al. 2017).…”
Section: Discussionsupporting
confidence: 62%
“…Thelephora ganbajun is a rare wild edible fungus that is distributed in pine forests in high-altitude areas of Yunnan Province, southwestern China [11][12][13][14][15]. In the present study, we found that T. ganbajun could accumulate zinc in the form of zinc-enriched polysaccharides.…”
Section: Introductionsupporting
confidence: 47%
“…The mating type genes regulate mating (hyphal fusion) and meiosis. Recent research has shown increasing evidence for mitochondrial DNA recombination under both laboratory and field conditions, though it is widely believed that the inheritance of mitochondrial DNA in fungi is uniparental and non-recombining (Wilson and Xu, 2012;Breton and Stewart, 2015;Xu and Wang, 2015;Wang et al, 2017). Indeed, mutation of a specific gene involved in sex-determination caused the rapid spread of multiple introns in the human pathogenic yeast Cryptococcus neoformans (Yan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%